On the sensitivity of structural turbulence uncertainty estimates to time and space resolution. (30th October 2021) - Gori, G.; Le Maître, O.P.; Congedo, P.M.
Abstract: This paper presents a sensitivity analysis of structural turbulence uncertainty estimates to time and space resolution of numerical computations. Turbulence uncertainty estimates are obtained by means of the Eigenspace Perturbation Method (EPM). Results show that, in general, one cannot expect the turbulence uncertainty estimates to be mesh and time-step independent based on the sole sensitivity analysis of the baseline solution. The recommendation is to carry out independent sensitivity studies, to guarantee that the confidence uncertainty estimates are well-predicted regardless of the space and time resolution. Highlights: Structural uncertainty inherent RANS turbulence closures challenges prediction The Eigenspace Perturbation Method is used to build a credibility indicator The sensitivity of the indicator to space/time resolution of simulations is analyzed Independent sensitivity studies of diverse EPM solutions are recommended